Cathodic corrosion: an electrochemical approach to capture Zintl compounds for powder materials1. Issue 10 (14th March 2015) - Yang, Yingchang; Qiao, Binghan; Wu, Zhengping; Ji, Xiaobo
<x xml:space="preserve">Abstract</x> Zintl compounds stimulated by cathodic corrosion have been introduced for the first time to turn bulk Sn and Pb into micro/nano powder materials.